Instytucja kary umownej w latach 1965–1989 — wybrane zagadnienia - Guzewicz, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The basis of this article is the analysis of the functioning of a contractual penalty in the years 1965–1989, i.e. from the time the Civil Code entered into force until the end of the Polish People’s Republic period. The research was carried out by means of analysing the legal provisions, the caselaw of the Supreme Court and the views of the doctrine. Its purpose is to reflect and draw conclusions on the functioning of the civil law institution — a contractual penalty — under authoritarian governments. The considerations were focused on selected problems, first of all concentrating on the Supreme Court’s case-law. Legal relations with the participation of socialized economy units become an important element of these considerations. The provisions of the Civil Code constitute the starting point, but they cannot be interpreted in isolation from the provisions of other normative acts that introduced special legal solutions in contracts with the participation of units of the socialized economy. The confrontation of theory and practice shows how the obligations imposed on entities of civil law are enforced. Against this background, issues of key importance for civil law emerge. They relate to the principles of concluding contracts, the performance of obligations, and the consequences of a failure to perform the contract.
Keywords: kara umowna; prawo cywilne; niewykonanie umowy; jednostki gospodarki uspołecznionej